Reducing The Financial Risk And Increasing The Output By Adopting And Suitable Locating Of Financial Strategies - Nazari, Reza; Asgar Zamani, Ali (European Journal of Sustainable Development, 2018)
The finance strategy is a dimension of strategy which is placed in finance management and different finance decisions should be adopted by mentioning the four types. The present study’s concentration is on defining and presenting the different financial strategies. Through the present article, the method of selecting and executing the financial strategies, the quality of managing the company, adopting the suitable strategies in financial risks, increasing the total risk and whole output have been explored. For this, the financial strategies were explored, and then the suitable strategies were presented for reducing the financial risks, total risk and increasing the output. Key Terms: Financial Strategies, Financial Supplying Strategies, Working Capital Strategies, Investment Strategies, Dividend Strategies